(untitled) (PANGEEA, 2025)
Abstract: This English-language obituary honors Academician Gheorghe Udubaşa (1938–2019), a prominent Romanian geologist who made significant contributions to mineralogy and geology in Romania and Europe. It outlines his education at the University of Bucharest and Heidelberg, his long career at the Geological Institute of Romania, leadership roles, and a prolific research record including numerous mineral discoveries and methodological advances. The piece also notes his recognition by the Romanian Academy and various scientific societies, reflecting on his influence on geology and science in Romania.